Halal Certification of Micro and Small Enterprises’ Food Products for Consumer Protection - Sakti, Muthia; Ramadhani, Dwi Aryanti (Amsir Law Journal, 2023)
This research aims to discuss the statutory regulations of halal certification. The study was performed through literature studies, especially on primary, secondary, and tertiary legal materials that describe legal protections for consumers and consideration of the halal certification. This study showed that micro and small enterprises’ food products are easy to verify about the halal food products, as long as the organization that assists the enterprises are legal entities. Micro and small enterprises (MSEs) should only make a statement letter of the halalness of a product that is verified and get assistance by Islamic social organizations or religious institutions that are legal entities and/or universities, government agencies, or business entities as long as they are partners with legal Islamic community organizations or Islamic religious institutions. However, regulations related to the halal statement of micro and small enterprise actors must still be reviewed and given special attention and supervision. In Indonesia, with the majority of the Muslim community, the guarantee of the halalness of a product and/or service is crucial. For this reason, the enactment of the Halal Product Guarantee Law is a form of state protection for Muslim consumers in Indonesia.___ References Books with an author: Amiruddin, A., & Asikin, Z. (2018). Pengantar Metode Penelitian Hukum. Jakarta: Raja Grafindo Persada. Aswirna, P., & Febriyanti, S. (2018). Pengabdian Berbasis Kebijakan Peningkatan Pemahaman Masyarakat tentang Pentingnya Mengkonsumsi Produk Halal bagi Pemuka Agama Islam Kota Padang. Padang: UIN Imam Bonjol. Barkatullah, A. H. (2008). Hukum Perlindungan Konsumen: Kajian Teoritis dan Perkembangan Pemikiran. Bandung: Nusa Media. Marzuki, P. M. (2005). Penelitian Hukum. Jakarta: Kencana Prenada. Rahardjo, S. (2003). Sisi-Sisi Lain dari Hukum di Indonesia. Jakarta: Kompas. Saebani, B. A. (2009). Metode Penelitian Hukum. Jakarta: Pustaka Setia. Shidarta, S. (2004). Hukum Perlindungan Konsumen Indonesia. Jakarta: Grasindo. Utsman, S. (2014). Metodologi Penelitian Hukum Progresif: Pengembaraan Permasalahan Penelitian Hukum Aplikasi Mudah Membuat Proposal Penelitian Hukum. Yogyakarta: Pustaka Pelajar. Journal articles: Ab Talib, M. S., & Mohd Johan, M. R. (2012). Issues in Halal Packaging: a Conceptual Paper. International Business and Management, 5(2), 94-98. Abd Rahman, A., Asrarhaghighi, E., & Ab Rahman, S. (2015). Consumers and Halal Cosmetic Products: Knowledge, Religiosity, Attitude and Intention. Journal of Islamic Marketing, 6(1), 148-163. Agustina, Y., Pratikto, H., Churiyah, M., & Dharma, B. A. (2019). Pentingnya Penyuluhan Sertifikasi Jaminan Produk Halal Untuk Usaha Kecil Menengah (UKM). Jurnal Graha Pengabdian, 1(2), 139-150. Ahmad, A., Pransisto, J., & Syahril, M. A. F. (2023). Perlindungan Hukum terhadap Konsumen Dalam Transaksi E-Commerce. Jurnal Litigasi Amsir, 10(3), 322-332. Anugrah, K. (2017). Potensi Pengembangan Wisata Halal Dalam Perspektif Dukungan Ketersediaan Restoran Halal Lokal (Non Waralaba) di Kota Gorontalo. Jurnal Pariwisata Pesona, 2(2), 1-12. Djakfar, I., & Isnaliana, I. (2021). Model Pendampingan Pengurusan Sertifikasi Produk Makanan Halal bagi UMKM dalam Mendukung Banda Aceh Menjadi Kota Wisata Halal. Wikrama Parahita: Jurnal Pengabdian Masyarakat, 5(1), 80-88. Erfan, M., Pransisto, J., & Syahril, M. A. F. (2023). Perlindungan Hukum Bagi Konsumen dari Peredaran Makanan Kedaluwarsa. Jurnal Litigasi Amsir, 10(2), 194-207. Faridah, H. D. (2019). Sertifikasi Halal di Indonesia: Sejarah, Perkembangan, dan Implementasi. Journal of Halal Product and Research, 2(2), 68-78. Fathoni, M. A. (2020). Potret Industri Halal Indonesia: Peluang dan Tantangan. Jurnal Ilmiah Ekonomi Islam, 6(3), 428-435. Giyanti, I., & Indriastiningsih, E. (2019). Effect of SME Food Entrepreneurs Knowledge on Halal Certification for Certified Awareness Using Partial Least Square. Jurnal Teknik Industri, 20(2), 140-151. Hartati, R. (2019). Peran Negara Dalam Pelaksanaan Jaminan Produk Halal. ADIL: Jurnal Hukum, 10(1). Ilyas, M. (2017). Sertifikasi dan Labelisasi Produk Halal Perspektif Maslahat. Jurnal Al-Qadau: Peradilan Dan Hukum Keluarga Islam, 4(2), 357-376. Izzuddin, A. (2018). Pengaruh Label Halal, Kesadaran Halal dan Bahan Makanan terhadap Minat Beli Makanan Kuliner. Jurnal Penelitian Ipteks, 3(2), 100-114. Jopie Gilalo, J., Sulistiyono, A., & Harahap, B. (2020). Tinjauan Yuridis dalam Bukti Hukum Konsumen dalam Makanan Halal. Jurnal Ilmiah Living Law, 12(1), 26-40. Kawata, Y., Htay, S. N. N., & Salman, A. S. (2018). Non-Muslims’ Acceptance of Imported Products with Halal Logo: a Case Study of Malaysia and Japan. Journal of Islamic Marketing, 9(1), 191-203. Khairunnisa, H., Lubis, D., & Hasanah, Q. (2020). Kenaikan Omzet UMKM Makanan dan Minuman di Kota Bogor Pasca Sertifikasi Halal. Al-Muzara’ah, 8(2), 109-127. Langvinienė, N., & Daunoravičiūtė, I. (2015). Factors influencing the success of business model in the hospitality service industry. Procedia-Social and Behavioral Sciences, 213, 902-910. Mawaddah, F. (2020). Constraints And Challenges of Halal Product Guarantee in the Syariate Area. SHIBGHAH: Journal of Muslim Societies, 2(1), 91-112. Mutmainah, L. L. (2018). The Role of Religiosity, Halal Awareness, Halal Certification, and Food Ingredients on Purchase Intention of Halal Food. Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 1(1), 33-50. Pujiono, A., Setyawati, R. F., & Idris, I. (2018). Strategi Pengembangan UMKM Halal di Jawa Tengah Dalam Menghadapi Persaingan Global. Indonesia Journal of Halal, 1(1), 1-7. Purwanda, S., & Wulandari, A. S. R. (2023). Socio-Legal Studies: Methodical Implications of Legal Development in Indonesia. Al-'Adl, 16(2), 152-163. Rahmawati, I. N., & Rukiyah, L. (2014). Win-Win Solution Sengketa Konsumen. Jakarta: Pustaka Yustisia. See also Kasim, A., & Heridah, A. (2020). The Region Governance Review of Barru Regency to Actualize Good and Clean Governments. Amsir Law Journal, 1(2), 61-69. Widayat, W., Sulardjaka, S., Al-Baarri, A. N., & Nurjannah, R. (2020). Pendampingan Sertifikasi Halal pada UMKM Hanum Food (Halal Certification Support in UMKM Hanum Food). Indonesia Journal of Halal, 3(1), 83-87. Yusoff, S. Z., Adzharuddin, N. A., & Bolong, J. (2014). Faktor Pencetus Perilaku Pencarian Maklumat Produk Halal Dalam Kalangan Keluarga Islam. Global Media Journal, 3(2), 69-82.